Authoring tool for digital storytelling in mykliks - How, Jiunchuan (Universiti Malaysia Sarawak, (UNIMAS), 2013)
MyKliks, a storytelling system is introduced to the community to empower the appropriate knowledge and skills to maximize the potential of ICT. It allows users to capture their local knowledge such as objects, events and moments by using the tablet in-built features. However, when users want to combine this knowledge into a digital storytelling, they are required to use third party authoring tool. This is due to the current MyKliks system does not have an appropriate authoring tool to enables users to produce the digital storytelling. Therefore an Authoring Tool is proposed to enhance the current MyKliks system. A literature reviews about the existing authoring tools in market has been done. Based on the analysis and research, the features of the existing authoring tool are learned and adopted into the proposed authoring tool for MyKliks. The features are categorized in several modules, which are Slide, Text, Graphics, Video and Others. For slide module, it allows users to insert new slide, delete slide and play digital storytelling. Text module allows users to insert text, move text, edit text and delete text while graphics module allows users to insert, move and delete images. Video module is responsible to insert and delete video, and lastly others module is responsible to save and open the existing digital storytelling. Lastly, system testing and evaluation is executed in order to ensure the system is bugfree. Comments from the testing are adopted as the limitation and future work for this system.